Increased levels of circulating platelet‐derived microparticles are associated with metastatic cutaneous melanoma. Issue 10 (9th May 2017) - Moreau, Joséphine; Pelletier, Fabien; Biichle, Sabeha; Mourey, Guillaume; Puyraveau, Marc; Badet, Nicolas; Caubet, Matthieu; Laresche, Claire; Garnache‐Ottou, Francine; Saas, Philippe; Seilles, Estelle; Aubin, François
Abstract: We investigated the plasma levels of PMPs in patients with 45 stage III and 45 stage IV melanoma. PMPs were characterised by flow cytometry and their thrombogenic activity. We also investigated the link between PMPs circulating levels and tumor burden. The circulating levels of PMPs were significantly higher in stage IV (8500 μL −1 ) than in patients with stage III (2041 μL −1 ) melanoma ( P =.0001). We calculated a highly specific (93.3%) and predictive (91.7%) cut‐off value (5311 μL −1 ) allowing the distinction between high‐risk stage III and metastatic stage IV melanoma. The thrombogenic activity of PMPs was significantly higher in patients with stage IV melanoma (clotting time: 40.7 second vs 65 second, P =.0001). There was no significant association between the radiological tumoral syndrome and the plasma level of PMPs. Our data suggest the role of PMPs in metastatic progression of melanoma.